Peculiarities of movement of track-and-field athletes and team sports players - Radziukynas, D.; Zilinskiene, N.; Kemeryte-Riaubiene, E.; Zilinskiene, R.; Wojnar, J. (Journal of Kinesiology and Exercise Sciences, 2014)
An athlete moves as an integral biomechanical system, yet depending on the specifics of a specific sports discipline, the activity of certain body parts is different. The performance of athletes in different track-and-field events and sports is determined by coordinative interaction of the legs, hands and other body parts, thus possible differences in their biodynamic structure and functional abilities may be assessed based on identical indices. Research aim. To determine kinematic and kinetic indices of a single vertical take-off and push-off of 20-23 year old male athletes engaged in track-and-field athletics (sprint and long jump) and sports (handball and basketball). Object of research. Studying the movement of athletes [track-and-field athletics (sprint and long jump) and sports (handball and basketball)] during a single vertical take-off and push-off. Research methods. 1. Tensodynamometry; 2. Mathematical statistics. Data processing carried out using PSS software (version 13.0). Research results. All kinematic and kinetic indices of a single vertical take-off and push-off of track-andfield athletes are similar to the ones of handball and basketball players, yet (p < 0.05) only the one of relative power (Wr, N/m/s/kg) is reliably better. When comparing the jump flight and height indices of the track-and-field athletes with basketball players, those indices are statistically reliably lower for the track-and-field athletes, yet the relative power of the single vertical take-off and push-off is higher (p < 0.05, p < 0.001). The basketball players` speed of body movement is reliably higher (p < 0.05) than for the handball players. The kinematic and kinetic indices of the single vertical take-off using both legs in all the three groups was reliably better (p < 0.001) when compared to the same indices of the single vertical push-off. The alteration of the quantitative ratio of those indices depends on the sports discipline specifics and reveals the level of individual motor abilities and body movement potential.